Cost-Effective Detection of SNPs and Structural Variations in Full-Length Genes of Wheat and Sunflower Using Multiplex PCR and Rapid Nanopore Kit - Ekaterina Polkhovskaya; Evgeniy Moskalev; Pavel Merkulov; Ksenia Dudnikova; Maxim Dudnikov; Ivan Gruzdev; Yakov Demurin; Alexander Soloviev; Ilya Kirov (Biology)
The rapid identification of allele variants in target genes is crucial for accelerating marker-assisted selection (MAS) in plant breeding. Although current high-throughput genotyping methods are efficient in detecting known polymorphisms, they are limited when multiple variant sites are scattered along the gene. This study presents a target amplicon sequencing approach using Oxford Nanopore Technologies (ONT-TAS) to rapidly sequence full-length genes and identify allele variants in sunflower and wheat collections. This procedure combines multiplex PCR and a rapid sequencing kit, significantly reducing the time and cost compared to previous methods. The efficiency of the approach was demonstrated by sequencing four genes (Ahasl1, Ahasl2, Ahasl3, and FAD2) in 40 sunflower genotypes and three genes (Ppo, Wx, and Lox) in 30 wheat genotypes. The ONT-TAS revealed a complete picture of SNPs and InDels distributed over the individual alleles, enabling rapid (4.5 h for PCR and sequencing) characterization of the genetic diversity of the target genes in the germplasm collections. The results showed a significant diversity of the Ahasl1/Ahasl3 and Wx-A/Lox-B genes in the sunflower and wheat collections, respectively. This method offers a high-throughput, cost-effective (USD 3.4 per gene) solution for genotyping and identifying novel allele variants in plant breeding programs.